An interview study of the care manager function-Opening the door to continuity of care for patients with depression in primary care - Camilla Udo; Irene Svenningsson; Cecilia Björkelund; Dominique Hange; Margareta Jerlock; Eva‐Lisa Petersson (Wiley, 2019)
Abstract Aim To explore experiences among patients with depression of contact with a care manager at a primary care centre. Design A qualitative explorative study. Methods During spring and summer 2016, 20 individual face‐to‐face interviews were conducted with patients with experience of care manager contact. The material was analysed using systematic text condensation. Results The participants described that having contact with a care manager was a support in their recovery process. Care became more available, and the structured continuous contact and the care manager's availability contributed to a trusting relationship. Having someone to share their burden with was a relief. However, it was described as negative when the care manager was perceived as inflexible and not open to issues that the participants felt a need to discuss. For the care manager contact to be successful, there is a need for flexibility and individually tailored contact.